Sukuk structure for deficit financing during Covid-19 crisis - Adam Sa'ad, Auwal; Aishath, Muneeza; Haron, Razali; Anwar, Hassan (Emerald Publishing Limited, 2022)
Purpose This paper identified the ṣukūk structure suitable for deficit financing during the COVID-19 crisis. The study also explored the relevant Sharīʿah contracts that could be utilized to issue ṣukūk that is suitable for various jurisdictions and corporations in handling deficit financing during the COVID-19 crisis. Design/methodology/approach The authors have adopted a qualitative research approach in which primary and secondary sources available on the subject were reviewed, especially a number of cases related to ṣukūk structures prior to and during the COVID-19 crisis and analyzed their performances and drawn their conclusions. Findings The outcome of this paper suggests that certain ṣukūk structures used during the COVID-19 crisis aimed primarily at financing deficit have been successful. Furthermore, these ṣukūk structures are relied very much on the obligator’s/issuer’s cash flow position. It has been revealed that if the ṣukūk is structured on equity-based contracts with lower repayment amount or no payment, it would not trigger default because the nature of this ṣukūk is the sharing of profit and loss, in accordance with a Sharīʿah rule that there will be compensation for any loss only if deliberate and notable negligence is proven. However, if it is debt based or ijarah and wakalah contracts, then the payment to ṣukūk holders ought to be made as agreed and if not, it will trigger default. This payment is to be made from the cash flow of the issuer and if there is an issue in the cash flow of the issuer due to COVID-19, consent from the ṣukūk holders needs to be obtained to reschedule payment as found in the case of the Garuda Indonesia ṣukūk . However, as found in MASB’s IMTN ṣukūk case, if the cash flow of the company is good, then the chances of default are very slim. However, so far, three new ṣukūk in the middle of COVID-19 were issued, one by a corporation and two issued by a sovereign, one of which addresses the liquidity issues during the pandemic, and all these proved that ṣukūk is definitely a viable alternative mode for deficit financing and a reliable option during the COVID-19 pandemic. Research limitations/implications This paper looked into the ṣukūk structure, especially the ṣukūk which are yet to mature and the new ṣukūk issued during the crisis caused by the COVID-19 pandemic. Practical implications It is anticipated that the outcome of this research will assist the stakeholders in ṣukūk markets to understand the ṣukūk impact on COVID-19 related deficit financing and suggest various structures that could be utilized in the ṣukūk market in an unprecedented situation such as the COVID-19 economic distress. Social implications Looking at the social aspect of ṣukūk markets, this paper has endeavored to provide solutions to the financing of deficit for social well-being as a tool to provide relief and social stability in the lives of the people. Originality/value The novel COVID-19 pandemic has caused unprecedented economic difficulties and market distress on a global scale; and this research sought to identify the relevant ṣukūk structures to be used for deficit financing during the pandemic crisis, especially the ṣukūk which are yet to mature and new ṣukūk issued during the pandemic crisis. The former includes HDFC Muḍārabah ṣukūk (2019) Maldives and MAHB ṣukūk /IMTN program (2010) Malaysia, while the latter includes IsDB Trust Certificates, Phase 2 of the tranches (2020), the Federal Government of Nigeria Road ṣukūk (May, 2020) and Sharj’ah Government two billion Dirham ṣukūk (June, 2020).